Nuclear architecture by RNA - Caudron-Herger, Maïwen; Rippe, Karsten (Current opinion in genetics & development, 2012)
The dynamic organization of the cell nucleus into subcompartments with distinct biological activities represents an important determinant of cell function. Recent studies point to a crucial role of RNA as an architectural factor for shaping the genome and its nuclear environment. Here, we outline general principles by which RNA organizes functionally different nuclear subcompartments in mammalian cells. RNA is a structural component of mobile DNA-free nuclear bodies like paraspeckles or Cajal bodies, and is involved in establishing specific chromatin domains. The latter group comprises largely different structures that require RNA for the formation of active or repressive chromatin compartments with respect to gene expression as well as separating boundaries between these.